Indeks Massa Tubuh terhadap Arus Puncak Ekspirasi Mahasiswi Universitas Jambi - harahap, huntari (LPPM Universitas Jambi, 2024)
ABSTRACT Background Peak flow respiratory rate is one of the tests used to assess lung function, monitor for diseases caused by pulmonary obstruction, and respond to pulmonary treatment. Many factors affect the peak expiratory flow which will also affect lung function mainly due to anthropometric differences. Aim The research objective was to determine the effect of body mass index on peak expiratory flow rate. Method forty-three women, inclusion criteria were in good health, did, n't have obstructive respiratory disorders, and did not smoke. The students measured height, weight, waist circumference, and peak flow respiratory rate using the Mini Wright Flowmeter. Result in the peak expiratory flow rate of female students (mean=228.37). There was no significant correlation between female students' peak expiratory flow and body mass index (p = 0.28, r = -0.19). Conclusions The effect of peak expiratory flow on body mass index is not statistically significant for students of the Faculty of Medicine, Jambi University,